2007
DOI: 10.1002/jcb.21036
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐proliferative effects of evodiamine on human prostate cancer cell lines DU145 and PC3

Abstract: Prostate carcinoma is one of the most common malignant tumors and has become a more common cancer in men. Previous studies demonstrated that evodiamine (EVO) exhibited anti-tumor activities on several cancers, but its effects on androgen-independent prostate cancer are unclear. In the present study, the action mechanisms of EVO on the growth of androgen-independent prostate cancer cells (DU145 and PC3 cells) were explored. EVO dramatically inhibited the growth and elevated cytotoxicity of DU145 and PC3 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 53 publications
(52 reference statements)
9
67
1
1
Order By: Relevance
“…For example, evodiamine induced cell cycle arrest in human colon LoVo cells at the S phase (24). The result of evodiamine cell cycle arrest at the G2/M phase is also consistent with other studies that evodiamine arrests the cell cycle at G2/M phase (8,11,13). These findings suggest that G2/M phase arrest is one of the mechanisms through which evodiamine induces cytotoxicity in SGC-7901 cells.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For example, evodiamine induced cell cycle arrest in human colon LoVo cells at the S phase (24). The result of evodiamine cell cycle arrest at the G2/M phase is also consistent with other studies that evodiamine arrests the cell cycle at G2/M phase (8,11,13). These findings suggest that G2/M phase arrest is one of the mechanisms through which evodiamine induces cytotoxicity in SGC-7901 cells.…”
Section: Resultssupporting
confidence: 90%
“…Evodiamine is a naturally occurring quinolone alkaloid found in the fruit of Evodia rutaecarpa. The data of several studies concerning its cytotoxic activity in cancer cells demonstrated that evodiamine inhibited the growth of a wide variety of tumor cells, including breast (8), thyroid (9), liver (10), prostate (11)(12)(13)(14), leukemic T-lymphocyte (5,15), melanoma (6,(16)(17)(18) cervical (19,20), colon (21)(22)(23)(24), colorectal (25) and lung cells (26) through induction of apoptosis, regulation of cell cycle and reduction of invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, evidence indicates that EVO possesses anticancer activities. EVO is reported to hinder tumor development by inhibiting cancer cell proliferation and inducing cell apoptosis in various types of cancer cells, such as lung (14), acute leukemia (15)(16)(17), prostate (18)(19)(20) and cervical (17). Yang et al reported that EVO can upregulate the expression of phosphatase shatterproof 1 (SHP-1) (21), which is the key gene of IL-6-induced signal transducer and activator of transcription signaling 3 (STAT3) signaling leading to the suppression of survival and proliferation in hepatocellular carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cytotoxicity of evodiamine and rutaecarpine on various human cancer cell lines has been extensively studied (Ogasawara at al., 2001;Fei et al, 2003;Liao et al, 2005;Xu et al, 2006;Adams et al, 2007). It has been reported that evodiamine inhibited the proliferation of a wide variety of tumor cells by inducing apoptosis via different mechanisms, including caspase-dependent and -independent pathways, the sphingomyelin pathway, and PI3K/Akt/caspase and Fas-L/NF-kB signaling pathways (Lee et al, 2006a;Kan et al, 2007;Wang et al, 2010;Huang et al, 2011). More recently, highly potent evodiamine derivatives were discovered as novel antitumor agents by systemic structure-activity relationship analysis and biologic evaluations (Dong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%